INFLUENCE OF MODES AND METHODS FOR POWDER ADDITIVE INTRODUCTION ON QUALITY OF BUILT-UP LAYER IN CARBON DIOXIDE MEDIUM - N. V. Spiridonov; V. V. Kurash; A. V. Kudina; V. V. Khrolenok; A. S. Nikitina (Наука и техника)
The paper investigates an influence of current strength and voltage on the height of a depositing bead and depth of main material penetration in case of surfacing in carbon dioxide medium. Dependence of a depositing bead height and depth of main material penetration has been determined in respect of various surfacing modes. On the basis of the analysis of the formed structures being surfaced with powder additive it has been shown that introduction of metal powders in the tail part of melted metal favours formation of qualitative fine grain structure that improves physical and mechanical characteristics of a melted metal.